STRUCTURAL EQUATION MODELING OF SALES PEOPLE PERFORMANCE IN THE COMPANY OF BUSINESS TO BUSINESS - Susilo, Andri Wibowo; Supit, Hengky; Astuti, Sri Wahyuni; Otok, Bambang Widjanarko (Acta Scientiae et Intellectus, 2024)
The purpose of this research examines the pattern of adaptive selling against performance of sales suite. By using Structural Equation Modeling (SEM), it reveals that sales people performance influenced by the ability to monitor and to modify motivation in practicing adaptive selling behavior. Therefore, there should be a training syllabus, which in the end can be used as an evaluation of the performance of employees.